Systematic Review of the Effectiveness of Using iPSC in Spinal Cord Injury - Ibrahim, Sabri; Ramadhan, Hafiz (Talenta Universitas Sumatera Utara, 2022)
Damage to the spinal cord is the pathological condition known as spinal cord injury (SCI) or spinal cord injury. This ailment, which not only causes neurological impairments but also places a significant psychological and social burden on patients, has grown to be one of the most challenging worldwide health issues. A successful stem cell-based treatment has just been created and could be the answer to this medical issue. It has been demonstrated that iPSC-dNSC stem cells are efficient at both reducing post-traumatic inflammatory conditions and kicking off neuronal cell regeneration at the location of SCI lesions. The aim of this study to investigate the the effectiveness of using iPSC in spinal cord injury. This study used the literature review method by discovering articles using the search engine Google Scholar, and PubMed. According to the search results, 413 articles were obtained in accordance with the title of the study, but 8 articles met the inclusion criteria in this study. The findings of this study showed that the iPSC methodology was applied, as well as the advantages and results of the procedure. Using iPSCs to treat SCI is still challenging and needs additional investigation.